Helitrons and Retrotransposons Are Co-localized in Bos taurus Genomes - Babii, A.; Kovalchuk, S.; Glazko, T.; Kosovsky, G.; Glazko, V. (Current Genomics, 2017)
Background: DNA transposons helitrons are mobile genetic elements responsible for major movements of the genetic material within and across different genomes. This ability makes helitrons suitable candidate elements for the development of new approaches of multilocus genotyping of livestock animals, along with the well-known microsatellite loci. Objective: We aimed to estimate the informativeness of helitron and microsatellite markers in assessing the consolidation and the
Keywords: Transposable elements